Car Rental Information System Using The Waterfall Method In One Of The Car Rental Companies - Dewi, Novita Puspita; Fauka, Ahfi; Parghani, Rizal; Lesmana, Berry (Journal of Economics, Management, and Entrepreneurship, 2025)
Car rental reservations are presently conducted only over WhatsApp. The absence of social media promotions has resulted in stagnant revenue for the company, and there is no established mechanism to streamline data collection and processing for the automobile rental industry. This research seeks to facilitate online car rentals for clients and to deliver information to them effectively, efficiently, and accurately. Furthermore, it aims to augment the company's revenue substantially. The Waterfall software development methodology was selected to emphasise the systematic processes involved in creating this information system. This study seeks to develop and construct an effective car rental information system. The deployment of this car rental information system will enhance operational efficiency in handling rentals, expedite the borrowing and returning processes, and improve the overall user experience.